HUBUNGAN KADAR ALBUMIN DAN INDEKS MASSA TUBUH PADA PASIEN HEMODIALISIS RUTIN DI RSUD ULIN BANJARMASIN - Nur M Faisal Ghani; Mohammad Rudiansyah; Dewi Indah Noviana Pratiwi; Nani Zaitun; Franciscus Xaverius Hendriyono (Homeostasis, 2022)
Malnutrition is most common risk in patients undergoing routine hemodialysis compared to other general popolation, malnutrition is a condition in which the body leses muscle and visceral protein reserves. Albumin levels and body mass index in routine hemodialysis patient, in this studi using a cross sectional study with Pearson product momment correlation test. This study used secondary data on routine hemodialysis patients and clinical pathology laboratory at Ulin Hospital Banjarmasin. The research method using random sampling, obtained as many  74 subjects with subject distribution of 92 peeople. The results of study obtained correlation value of albumin levels and body mass index with a value of p =0.7 and a value of r = -0.030